A nesting aggregation of the solitary bee Megachile atrata (Hymenoptera: Megachilidae) in the Philippines - Starr, Christopher K. (Journal of Melittology, 2017)
A nesting aggregation of Megachile (Creightonella) atrata Smith in the Philippines comprised almost 300 active nests.  The bees in rapid flight resemble the hornet Vespa tropica Linnaeus. The nest structure is similar to that reported for M. (C.) frontalis (Fabricius) in New Guinea.